(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
In this essay we will try to make a connection between two decisions pronounced by the Italian constitutional Court in the 2018-2019 period on the matter of assisted suicide. We argue that sentence n. 242 of 2019 is far from providing a definitive solution to the ongoing debate on assisted suicide. Indeed, not only has the Court referred the matter back to the legislator multiple times, but all “cases” that do not perfectly fit in the “general” case considered in the sentence will likely appeal to the courts, even at the constitutional level.